Numerical modeling of pulsatile blood flow through a mini-oxygenator in artificial lungs. (September 2021) - Tang, Tao-Qian; Hsu, Sheng-Yen; Dahiya, Anurag; Soh, Chang Hwei; Lin, Kuang C.
Highlights: Investigating the effect of pulsating blood flow on oxygen transfer in oxygenators. Using CFD to elucidate in-vitro studies that reported divergent outcomes. Identifying operational parameters of blood flows that influence the oxygen transport. Quantitative and qualitative comparisons of the predicted results with experiments. Abstract: While previous in vitro studies showed divergent results concerning the influence of pulsatile blood flow on oxygen advection in oxygenators, no study was done to investigate the uncertainty affected by blood flow dynamics. The aim of this study is to utilize a computational fluid dynamics model to clarify the debate concerning the influence of pulsatile blood flow on the oxygen transport. The computer model is based on a validated 2D finite volume approach that predicts oxygen transfer in pulsatile blood flow passing through a 300-micron hollow-fiber membrane bundle with a length of 254 mm, a building block for an artificial lung device. In this study, the flow parameters include the steady Reynolds number ( Re = 2, 5, 10 and 20), Womersley parameter ( Wo = 0.29, 0.38 and 0.53) and sinusoidal amplitude ( A = 0.25, 0.5 and 0.75). Specifically, the computer model is extended to verify, for the first time, the previously measured O2 transport that was observed to be hindered by pulsating flow in the Biolung, developed by Michigan Critical Care Consultants. A comprehensive analysis is carried out on computed profiles and fields of oxygen partial pressure ( P O2 ) and oxygen saturation ( S O2 ) as a function of Re, Wo and A . Based on the present results, we observe the positive and negative effects of pulsatile flow on P O2 at different blood flow rates. Besides, the S O2 variation is not much influenced by the pulsatile flow conditions investigated. While being consistent with a recent experimental study, the computed O2 volume flow rate is found to be increased at high blood flow rates operated with low frequency and high amplitude. Furthermore, the present study qualitatively explains that divergent outcomes reported in previous in vitro experimental studies could be owing to the different blood flow rates adopted. Finally, the contour analysis reveals how the spatial distributions of P O2 and S O2 vary over time.